Rancang Bangun Sistem Monitoring Suhu dan Kelembaban Kandang Bebek Berbasis Internet of Things - Malpindo Ambarita; I Putu Gede Budisanjaya; Yohanes Setiyo; I Putu Surya Wirawan; Radi (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2025)
The main challenge in duck farming is maintaining the environmental conditions of the cage, especiallytemperature and humidity to remain optimal. The purpose of designing a duck cage temperature andhumidity monitoring system based on the Internet of Things. The Design Stages consist of FunctionalDesign and Structural Design and Performance Test of the Internet of Things-based temperature andhumidity monitoring system. The heating lamp works according to the design, turning on if the temperatureis less than 27°C and humidity is more than 80% and turning off if the temperature is more than 30°C andhumidity is less than 60%. This maintains ideal temperature and humidity conditions for duck livestock. Inthe DHT11 sensor test on temperature measurement, there was an error difference of 0.43 and an errorpercentage of 1.65%, while in humidity measurement there was an error difference of 0.44 and an errorpercentage of 0.53%. So it can be concluded that the system is quite accurate in measurements and can beused to monitor the temperature and humidity of the duck house in real-time.